Film-forming amines adsorption and corrosion kinetics on carbon steel surface in neutral solution investigated by EIS and PM-IRRAS analysis. (1st March 2023) - Jero, Deni; Caussé, Nicolas; Marsan, Olivier; Buffeteau, Thierry; Chaussec, Fabrice; Buvignier, Amaury; Roy, Marion; Pébère, Nadine
Highlights: EIS is used to follow the OLDA adsorption kinetic onto carbon steel surface from 2 min to 140 min of immersion. OLDA adsorption and corrosion processes occur simultaneously from the beginning of immersion. OLDA preferentially adsorbed on the corrosion products. For short immersion time, the barrier layer thickness is around 10-20 nm. With increasing temperature, corrosion and, as a consequence, barrier layer thickness increases. Abstract: N-oleyl-1, 3-propanediamine (OLDA) is one of the most used film-forming amines (FFAs) for the corrosion protection of carbon steel circuits of a wide range of industrial plants. The present work focused on the study of OLDA adsorption kinetics onto the carbon steel surface by electrochemical impedance spectroscopy (EIS). The diagrams were obtained in a 200 mg.kg −1 NaCl with and without OLDA for immersion times ranging from 2 min to 140 min and for two temperatures (25°C and 50°C). It was shown that, from the beginning of immersion (2 min), OLDA adsorption and corrosion occurred simultaneously on the carbon steel surface. With increasing immersion time, a dynamic and competitive process between both phenomena was established until a steady-state was reached and the corrosion was slowed down. Ex situ Raman spectroscopy analyses revealed a heterogeneous distribution of the OLDA molecules on the surface with a preferential adsorption on the corrosion products, mainly γ-FeOOH. E x situ Polarization Modulation Infrared Reflection Absorption Spectroscopy (PM-IRRAS) analyses confirmed the formation of mixed barrier layers (OLDA molecules/corrosion products) whose thickness increased with time and temperature.